Expression and purification of full-length Alanyl-tRNA-synthetase from Thermus thermophilus HB27 - Rybak, M.Yu.; Priss, A.E.; Gudzera, O.I.; Kovalchuk, A.O.; Kryklyvyi, I.A.; Tukalo, M.A. (Вiopolymers and Cell, 2018)
Aim. To gain insight into structural and functional properties of alanyl-tRNA,synthetase (AlaRS), we genetically engineered constructs for expression and purification of full-length AlaRS and checked its activity in aminoacylation assays. Methods. The genomic DNA for the AlaS gene from the T. thermophilus (HB 27 strain) was amplified by PCR and cloned into vectors with and without a histidine tag. To optimize conditions for the protein expression in E. coli and to develop efficient purification procedure, the molecular biology techniques were applied. AlaRS was purified by affinity and size-exclusion chromatography. The molecular weight of enzyme was determined by gel filtration. Results. The expression and purification conditions for recombinant AlaRS were optimized. Approximately 1.5 mg of the pure active recombinant enzyme can be obtained from 1 L of bacterial culture. AlaRS from T. thermophilus is a dimer in solution with an experimental MW of 204 kDa. Conclusions. The purified recombinant enzyme will be used for further studies on the functional kinetics and structure of the crystal complex with tRNA. Мета. Для детального вивчення структурних та функціональних властивостей аланіл-тРНК-синтетази (АлаРС) було створено генно-інженерну конструкцію для експресії та очищення повнорозмірної синтетази та перевірено її активність у реакції аміноацилювання. Методи. Ген AlaS з T. thermophilus (штам HB27) геномної ДНК ампліфікували за допомогою ПЛР з відповідними праймерами та клонували у вектор з та без гістидинової послідовності. Для оптимізації умов експресії білка в E.coli та розробки ефективної процедури очищення були застосовані сучасні методи молекулярної біології. AлаРС очищали методами афінної хроматографії та гель-фільтрації. Молекулярна маса ферменту визначалася на гель-фільтраційній колонці. Результати. Умови експресії та очистки рекомбінантної АлаРС були оптимізовані. Близько 1,5 мг чистого рекомбінантного активного ферменту можна одержати з 1 л бактеріальної культури. АлаРС з T. thermophilus є димером у розчині з експериментальною масою 204 кДа. Висновки. Отриманий рекомбінантний фермент буде використовуватися для подальших експериментів з функціональної кінетики та структурних досліджень кристалічного комплексу з тРНК. Цель. Для детального изучения структурных и функциональных свойств аланил-тРНК-синтетазы (АлаРС) было создано генно-инженерную конструкцию для экспрессии и очистки полноразмерной синтетазы и проверено ее активность в реакции аминоацилирования. Методы. Ген аlaS из геномной ДНК T. thermophilus (штамм HB27) амплифицировали с помощью ПЦР с соответствующими праймерами и клонировали в вектор с и без гистидиновой последовательностью. Для оптимизации условий экспрессии белка в E. coli и разработки эффективной процедуры очистки были применены современные методы молекулярной биологии. AлаРС очищали методами аффинной хроматографии и гель-фильтрации. Молекулярная масса фермента определялась на гель-фильтрационной колонке. Результаты. Условия экспрессии и очистки рекомбинантной АлаРС были оптимизированы. Около 1,5 мг чистого рекомбинантного активного фермента можно получить с 1 л бактериальной культуры. АлаРС с T. thermophilus является димером в растворе с экспериментальной массой 204 кДа. Выводы. Полученный рекомбинантный фермент будет использован для дальнейших экспериментов с функциональной кинетики и структурных исследований кристаллического комплекса с тРНК